2019
DOI: 10.1111/wej.12540
|View full text |Cite
|
Sign up to set email alerts
|

Removal of polycyclic aromatic hydrocarbons from wastewater using dual‐mode ultrasound system

Abstract: Treatment of wastewater using ultrasound systems is gaining increasing interest due to its effectiveness for a wide range of pollutants and no secondary pollutant production. This paper proposes two ultrasound systems operating at different ranges of electrical power and frequency developed to remove toxic polycyclic aromatic hydrocarbon (PAH) compounds in wastewater. Both light molecular weight (LMW) and high molecular weight (HMW) compounds were degraded using the developed systems. However, HMW compounds we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Among other PAHs, naphthalene is the most widespread PAH in the effluent streams of the petroleum and coal industries, which is definitely related to its relative higher water solubility in comparison to other PAHs [8]. Over the years, processes have been developed for the removal of PAHs from contaminated waters including the ultrasonic process [9], adsorption [7], biodegradation [10], pulse radiolysis [11], and heterogeneous photocatalysis [7]. To date, TiO 2 has proven its efficacy in the photocatalytic oxidation of various PAHs and especially in the remediation of naphthalene [12].…”
Section: Introductionmentioning
confidence: 99%
“…Among other PAHs, naphthalene is the most widespread PAH in the effluent streams of the petroleum and coal industries, which is definitely related to its relative higher water solubility in comparison to other PAHs [8]. Over the years, processes have been developed for the removal of PAHs from contaminated waters including the ultrasonic process [9], adsorption [7], biodegradation [10], pulse radiolysis [11], and heterogeneous photocatalysis [7]. To date, TiO 2 has proven its efficacy in the photocatalytic oxidation of various PAHs and especially in the remediation of naphthalene [12].…”
Section: Introductionmentioning
confidence: 99%
“…17) these are released into receiving bodies. Although some studies aimed at increasing the degradation of some PAHs (NAP, PHE, ANT, PY and ACT) with sonication have appeared, these have been limited to only a few of those generally present (3)(4)(5) [11,13,[18][19][20].…”
Section: Inmentioning
confidence: 99%
“…These trace pollutants are an important issue for recycling of the wastewater. Although various technologies for petrochemical treatment have been investigated: biological treatment acid and surfactant treatment, ultrasonic treatment, ozone treatment, electrochemical treatment and electroflotation [5,6]. Among them, ultrasonic treatment has been used widely because of its relatively low processing cost and high efficiency of reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was also found that ultrasonication can be effective when it is combined with membrane techniques because of the so-called fouling limitation [45][46][47]. According to literature data, ultrasonication could be effective also in BPA and PYR removal from the environment [4,8,9,21,[48][49][50][51][52][53]. However, there is a lack of knowledge about the removal of BPA and PYR from the retention basins water matrices by using ultrasound, thus, the study is the first research on determining ultrasound (US) technology efficiency for BPA and PYR removal from highway retention basin.…”
Section: Introductionmentioning
confidence: 99%